OPTIMALISASI GOOGLE SITES SEBAGAI MEDIA PEMBELAJARAN UNTUK MATERI MITIGASI BENCANA LONGSOR PADA SISSWA KELAS XI SMA DI KOTA SAMARINDA - Sabrina Oktaviani; Mei Vita Romadon Ningrum; Juwari; Arum Sekar Kedhaton (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Geography instruction on landslide disaster mitigation at the high school level is still dominated by conventional methods, resulting in students’ understanding being abstract and lacking in context. This situation is suboptimal, given that the city of Samarinda faces a high risk of landslides, including in school environments. This study aims to develop and assess the feasibility of Google Sites-based learning materials on landslide disaster mitigation for 11th-grade high school students in Samarinda. This study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at State High School 13 Samarinda and IT Granada High School in Samarinda. Research instruments included expert validation forms for the media and content, as well as student response questionnaires. Data were analyzed using quantitative descriptive methods. The results indicate that the Google Sites-based media received a “highly feasible” rating based on expert validation and elicited positive responses from students. This media is capable of increasing student interest, facilitating understanding of the material, and supporting more interactive and flexible learning.